2019
DOI: 10.1021/acs.joc.9b00151
|View full text |Cite
|
Sign up to set email alerts
|

Unified Protocol for Fe-Based Catalyzed Biaryl Cross-Couplings between Various Aryl Electrophiles and Aryl Grignard Reagents

Abstract: The combination of commonly used FeCl3/SIPr with Ti­(OEt)4/PhOM enabled a highly general iron-based catalyst system, which could efficiently catalyze the biaryl coupling reaction between various electrophiles (I, Br, Cl, OTs, OCONMe2, OSO2NMe2) and common or functionalized aryl Grignard reagents with high functional group tolerance. Selective couplings of aryl iodides and bromides over the corresponding oxygen-based electrophiles have been achieved, and thus a terphenyl acid intermediate for anidulafungin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…13 C­{ 1 H} NMR (101 MHz, CDCl 3 ): δ 170.5, 159.3, 138.9, 135.5, 132.4, 130.1, 130.0, 129.7, 128.7, 127.2, 113.9, 55.2, 26.6 ppm. The spectroscopic data for this product match the literature data …”
Section: Methodssupporting
confidence: 82%
“…13 C­{ 1 H} NMR (101 MHz, CDCl 3 ): δ 170.5, 159.3, 138.9, 135.5, 132.4, 130.1, 130.0, 129.7, 128.7, 127.2, 113.9, 55.2, 26.6 ppm. The spectroscopic data for this product match the literature data …”
Section: Methodssupporting
confidence: 82%
“…Our study is based on the assumption that the difficulty of the Fe-catalyzed ortho C–H arylation of benzamides should lie not in the steric hindrance but in the ortho C–H deprotonative ferration of the amides because our previous findings indicated that two 2-substituted aryl Grignard reagents, after being mediated by Ti­(OR) 4 , could be facilely assembled into biaryls via a Fe-catalyzed oxidative coupling . After a series of attempts (see Table S1), we found that an unprecedented mixed titanate obtained by mixing 0.6 equiv of Ti-1 , 1.2 equiv TMPMgCl·LiCl, and 1.2 equiv ArMgX enabled the expected arylation in high yield (Scheme ).…”
mentioning
confidence: 99%
“…135,358−360 We have classified the various reactions into four main pathways, namely: (1) regioselective aromatic functionalization with DoM and/or AoF rearrangement, (2) DoM followed by annulation/cyclization, (3) combined DoM-CC reactions, and 362 synthesized the tetracyclic A/B/C/D ring core of the antitumor agent camptothecin (327) using a combined DoM/transition metal-catalyzed CC approach in seven steps and 11% overall yield (Scheme 81). The design is based on the initial coupling of 321, prepared by AoF rearrangement of quinoline 2-O-carbamate 319, with organozinc species (formed from 322 and ZnBr 2 ) to give 323, leading to the formation of the C-ring by simple functional group manipulation and cyclization (326). The simplicity of the steps, the ready availability of starting materials for both A/B-and Dring fragments by DoM chemistry, and the potential for further modifications of the D-ring allow further synthetic studies of camptothecin.…”
Section: Oam In the Synthesis Of Bioactive Molecules Natural Products...mentioning
confidence: 99%
“…Wang et al 326 reported a Fe/Ti-cocatalyst system that efficiently catalyzed the biaryl couplings between ArOAms and aryl Grignard reagents (Scheme 62). the Grignard reagents to these groups detected.…”
Section: Cross-coupling (Cc) Reactions Involving Aroammentioning
confidence: 99%
See 1 more Smart Citation